Populations of swans at the Ouse Washes, England - Cadbury, C J (Wildfowl, 1975)
Since 1967 the Bewick's Swans Cygnus columbianus bewickii at the Ouse Washes have represented at least 14% of those wintering in North-west Europe and 45% of the population in Britain and Ireland. Maximum numbers have tended to increase and in three winters since 1969-1970 over 1,000 have occurred at one time. Between 1954 and 1974 there was more than a four-fold increase in the usage of the Ouse Washes by this species. The provision of supplementary food, starting in the 1971-1972 winter, together with freedom from disturbance resulted in a marked concentration of Bewick's Swans on the Welney refuge at the expense of other areas on the Ouse Washes which had previously been favoured. Deep flooding and freezing forced Bewick's Swans off the washes and passage birds were not attracted when there was little flooding. The population wintering at Slimbridge is relatively discrete from that at the Ouse Washes. Influxes were associated with severe winters on the Continent which displaced birds from the Netherlands. The mean proportion of cygnets over the winters 1964-1975 was only 15% compared with 24% in the 1953-1964 period. It is suggested that recruitment has been insufficient to maintain the Bewick's Swan population wintering in North-west Europe at its 1955-1956 level of at least 7,000. The populations of Mute C. olor and Whooper Swans C. cygnus cygnus wintering at the Ouse Washes represent about 1% of their respective populations in Britain and Ireland. The herd of Whooper Swans is the southernmost regular wintering one in England and may originate from a Scandinavian or Russian breeding population rather than Iceland. Usage of the Ouse Washes by Whooper Swans has increased significantly in recent years. The distribution of both Mute and Whooper Swans of the area changed in response to supplementary feeding with grain on the Welney refuge. The relative numbers of Whooper Swans to Bewick's at the Ouse Washes have changed from approximate equality in the 1938-1952 period to 1:33 subsequently. On the other hand the number of Whooper Swans has increased in relation to Mute Swans since 1964.